The Effect Of Thickness Reduction On Microstructure And Mechanical Propertiesof Cold Rolled And Cryorolled Low Carbon Steel - Mohammed Kassim, Mohammed Zul Azeem (Universiti Sains Malaysia, 2018)
The low carbon steel has very extensive application in the industrial field. Its limited strength becomes the obstacle to develop its potential applications. In recent years, ultrafine grained (UFG) structural materials have been studied aggressively, because they are expected to provide superior mechanical properties. The present work investigated the microstructure and mechanical properties of cold rolled and cryorolled low carbon steel at different thickness reduction. Firstly, low carbon steel was heat treated at 550 ºC for 60 minutes. For cryorolling, sample was dipped in the liquid nitrogen for 10 minutes before rolled. Then both cold rolled and cryrolled samples were rolled at different thickness reduction; 50%, 70%, 80% and 90%. Microstructure, crystallite size, strain, dislocation density and mechanical properties for both cold rolled and cryorolled low carbon steel at different thickness reduction were investigated using scanning electron microscope (SEM), X-ray Diffraction (XRD), Vickermicrohardness and tensile test. All the samples showed severely deformed grains which were elongated along the rolling direction. Cryorolled low carbon steel showed the finest grain size compared to the cold rolled low carbon steel with average grain size of 8.06 µm at 90% reduction. The pearlite started to break at 70% thickness reduction for both cold and cryorolled low carbon steel. Amount of cementite increases with increasing thickness reduction. Cryorolled low carbon steel have finer crystallite size, higher micro strain and higher dislocation density for all reduction compared to cold rolled low carbon steel. Tensile strength, yield strength and hardness shows increasing trend while ductility decrease with increasing thickness reduction and cryorolled at 90% thickness reduction showed the highest tensile strength, yield strength and hardness with value of 828.35 MPa, 810 MPa and 208.5 Hv.